Comparison of physical properties of extemporaneous oral suspension with suspending agent pulvis gummi and xanthan gum using paracetamol as model drug - Widiyastuti Lina; Tsalasani Zulfaidah Nanda; Amani Dinda Wifayatul; Annisa Alifia Nur’ (BIO Web of Conferences)
Contemporary paracetamol suspensions are made because some drug-active substances have a solubility that is practically insoluble in water but is needed in liquid form. Suspending agent is required to increase the low viscosity to prevent cake. Therefore, knowledge is needed about the ratio of PGA and xanthan gum as a suspending agent that can increase viscosity and the suspension's stability. The desired physical properties are that the suspension has particles that do not settle quickly and are easily redispersed. The study compared the physical properties produced by suspending agents PGA and xanthan gum. This research used an experimental method with descriptive data processing. In the study, six formulas were made to observe the appearance, color, smell and taste, pH value, particle size, and sedimentation volume formed, and the dispersibility of each formula was tested. Based on the study's results, it is known that the viscosity of the suspension with PGA has a higher value than that of Xanthan Gum. This is due to the ability of sedimentation volume and dispersibility time, which is faster because it has a larger particle size.